1965
DOI: 10.1128/aem.13.2.208-211.1965
|View full text |Cite
|
Sign up to set email alerts
|

Production of Aflatoxins in Submerged Culture1

Abstract: Aflatoxins can be produced on a synthetic medium in submerged culture. Glucose, sucrose, or fructose are the preferred carbon sources, and Casamino Acids are the preferred nitrogen source. Ammonia is almost as good a nitrogen source. Zinc is required at levels of at least 0.4 mg per liter. Concentrations of aflatoxin of 60 to 80 mg per liter (as determined by optical-density measurements of a chloroform extract of the unfiltered broth) can readily be obtained in indented shake flasks; somewhat lower yields wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 5 publications
6
58
0
Order By: Relevance
“…The widely differing amounts of aflatoxins produced in conjunction with the sugars and sugar derivatives examined in the present study have been noted by other investigators (Mateles and Adye 1965;Davis a n d Diener 1968;Abdollahi and Buchanan 1981b;Prasad 1983). The reason for these differences is not known, but could reflect differences in the mechanisms or relative rates of catabolism among the compounds.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The widely differing amounts of aflatoxins produced in conjunction with the sugars and sugar derivatives examined in the present study have been noted by other investigators (Mateles and Adye 1965;Davis a n d Diener 1968;Abdollahi and Buchanan 1981b;Prasad 1983). The reason for these differences is not known, but could reflect differences in the mechanisms or relative rates of catabolism among the compounds.…”
Section: Discussionsupporting
confidence: 76%
“…Various investigators have demonstrated that the synthesis of aflatoxins is dependent on the identity (Mateles and Adye 1965;Davis and Diener 1968; Abdollahi a n d Buchanan 1981b; Prasad 1983) and concentration (Mateles a n d Adye 1965; Davis et al 1966Davis et al , 1967Hsieh and Mateles 1971;Shih a n d Marth 1974a, 1974b; Applebaum a n d Buchan a n 1979; Buchanan a n d Houston 1982) of available carbon sources. Abundant aflatoxin production was associated generally with elevated levels of specific carbohydrates, and Buchanan (1981a, 1981b) hypothesized that the active catabolism of suitable carbohydrates was involved in the regulation of aflatoxin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Clade B contains 11 gene clusters (4, 5, 9, 10, 11, 20, 23, 31, 37, 48 and 50). The characteristic of this group is low gene expression in liquid shake culture medium [A&M medium (Mateles and Adye, 1965) experiments and laeA experiments]. The expression values in other experiments were also not as high as those associated with genes in clade A.…”
Section: Transcriptional Analysis Of 55 Predicted Gene Clusters In Amentioning
confidence: 99%
“…A total of five different cell culture conditions known to influence AF biosynthesis (Mahoney and Molyneux, 2004;Price et al, 2005) were tested for their effect on the accumulation of CPA and AF. NRRL3357 was grown in either A&M medium (Mateles and Adye, 1965) or A&M medium modified for carbon source (50 g/L), nitrogen source (3 g/L), pH or the presence of antioxidants. All media were buffered at pH 4.5 with 100 mM citric acid, except for the pH 8.0 treatment, which was buffered with 100 mM tris(hydroxymethyl)aminomethane (Tris).…”
Section: Culture Media For Cpa and Af Productionmentioning
confidence: 99%
“…However, the importance of Ca 2¦ , which is an important second messenger mediating diverse biological activities, has not been firmly established in the production of secondary metabolites by fungi, and its role in aflatoxin production remains controversial. While both calcium and iron were reported to exert meagre influences on aflatoxin formation (Mateles and Adye 1965;Lee et al 1966), Tulpule (1969) as well as Maggon et al (1977) reported that the absence of calcium from culture media results in decreased aflatoxin production. Enhanced [ 14 C]-acetate incorporation into aflatoxins was also observed in the presence of calcium by stationary phase cultures of A. parasiticus (Gupta et al 1975).…”
Section: Introductionmentioning
confidence: 99%